Advances in global leadership. Vol. 3 - William H. Mobley; Peter W. Dorfman (Advances in global leadership,, 2003)
The global shortage of effective business leaders makes urgent the search for new insights about the nature of global leadership and the best means of developing such leaders. This text is a response to this urgent need. The rapid globalization of the economy places business leaders in new and demanding international settings and requires them to work across cultures. Volume 3 of Advances in Global Leadership presents original papers on the psychology of global leadership and the development of international and global leaders. Chapters are authored by academics, business leaders and consultants throughout the world who bring their various insights into global leadership.